Um estudo sobre o fenômeno migratório enquanto dínamo do programa de contrarreforma agrária no Brasil (1974-1985) - Araújo, Marco Aurélio Corrêa de (2022)
This doctoral thesis is focused on an investigation of part of the historical trajectory of the Superintendence for Development of the Midwest Region (SUDECO), aiming to understand the actions of the Brazilian State - through both names linked to institutional management and the actions of the various responsible bodies for the control of internal migrations in the national territory -, aimed at the regional territory, during the context of action of the so-called “special programs”. In this scenario, the State's search, allied with the owners of capital, for the control of social layers that are “threatening” to the current political and economic system can be seen. In this context, the aim is, fundamentally, to verify how this issue of internal migration is of paramount importance for understanding the consolidation of monopoly capital in the region in focus and, consequently, for the achievement of a counter-agrarian reform program.